Prevalence and Risk Factors of Covid-19 Mortality and its Impact on Social Life of Pakistani Population - Sarah Arif, Tayyaba Zia, Zohaib Qayyum, Ghulam Mustafa, Muhammad Ateeq, Sadia Farhad, Sudhair Abbas Bangash, Anila Farid, Somayia Hafeez, Farhat R Malik, Fares M Muthanna (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Currently, the world is in a challenging situation due to Covid-19. The ministry of health in Pakistan reported the first case of Covid-19 on 26th February 2020 in Karachi whereas on the same day in Islamabad, the second case was confirmed in Pakistan. Objective: To assess the prevalence and risk factors of covid-19 mortality and its impact on social life of Pakistani population Methodology: This retrospective study was carried out at the Department of Pathology, Gomal Medical College, Medical Teaching Institute, Dera Ismail Khan, Pakistan for a period of ten months from March 2021 to December 2021. All the data was taken from the hospital record to determine the prevalence and risk factors associated with the mortality of covid-19. For determining the influence of covid-19 on the social life, online survey was conducted. Data was entered and analyzed by using SPSS version 24. Results: In the current study, the overall prevalence of covid-19 was 6%. The most common risk factors associated with the covid-19 was Diabetes mellitus in 25 (71.43%) subjects, hypertension in 22 (62.86%), ischemic heart disease in 16 (45.71%) while chronic liver disease was observed in 3 (8.57%) subjects. According to the survey, 420 (70%) participants thought that covid-19 will be controlled worldwide while 450 (75%) subjects thought that covid-19 will be controlled in Pakistan. Worry of contracting covid-19 even with protective measures was observed in 420 (70%) subjects. Conclusion: Our study reported that the prevalence of covid-19 was 6%. Diabetes mellitus, hypertension and ischemic heart disease were the major associated risk factors with the mortality of covid-19 and the overall impact of covid-19 on social life of Pakistani population was not good according to our study.